2022
DOI: 10.1021/jacs.2c01991
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne-Tagged Raman Probes for Local Environmental Sensing by Hydrogen–Deuterium Exchange

Abstract: Alkyne-tagged Raman probes have shown high promise for noninvasive and sensitive visualization of small biomolecules to understand their functional roles in live cells. However, the potential for alkynes to sense cellular environments that goes beyond imaging remains to be further explored. Here, we report a general strategy for Raman imaging-based local environment sensing by hydrogen–deuterium exchange (HDX) of terminal alkynes (termed alkyne-HDX). We first demonstrate, in multiple Raman probes, that deutera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…With similar targeted reactions, triple-bond Raman probes with the peak-shift principles have also been rationally designed and developed for sensing pH, fluoride, and metal ions . Recently, the isotope exchange reactions (especially the H/D exchange) have been harnessed on the terminal alkynes for both two-color imaging and cellular environmental sensing applications. , The H/D exchange reaction results in the dramatic alkyne Raman peak shift (>130 cm –1 ) due to both the large mass difference between D and H and the quantum coupling between the alkyne and the adjacent CD. In addition to chemical reactions, Raman peak frequency can also be tuned by the surrounding physical environment.…”
Section: Functional Raman Imaging Probesmentioning
confidence: 99%
“…With similar targeted reactions, triple-bond Raman probes with the peak-shift principles have also been rationally designed and developed for sensing pH, fluoride, and metal ions . Recently, the isotope exchange reactions (especially the H/D exchange) have been harnessed on the terminal alkynes for both two-color imaging and cellular environmental sensing applications. , The H/D exchange reaction results in the dramatic alkyne Raman peak shift (>130 cm –1 ) due to both the large mass difference between D and H and the quantum coupling between the alkyne and the adjacent CD. In addition to chemical reactions, Raman peak frequency can also be tuned by the surrounding physical environment.…”
Section: Functional Raman Imaging Probesmentioning
confidence: 99%
“…High reactivity for alkyne C(sp)-deuteration under neutral conditions would be favourable for the selective deuteration of alkyne-tagged probes for Raman imaging. 30,31…”
Section: Resultsmentioning
confidence: 99%
“…The development of new Raman probes and analytical methods should further expand the potential of Raman spectroscopy for chemical biology research. For example, recently, Wei et al reported a new method for Raman imaging-based local environment sensing via hydrogen–deuterium exchange (HDX) of the terminal alkyne tag . This work demonstrates that UV-induced thymidine dimer formation can be detected by alkyne-HDX from EdU-labeled cells.…”
Section: Future Perspectivesmentioning
confidence: 99%